2005
DOI: 10.1002/art.21043
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of recommendations to prevent reactivation of latent tuberculosis infection in patients treated with tumor necrosis factor antagonists

Abstract: Objective. To investigate the impact of official recommendations regarding the management of latent tuberculosis (TB) infection on the rate of active TB in patients receiving treatment with tumor necrosis factor (TNF) antagonists.Methods. Data on active TB rates and on screening and treatment of latent TB infection were extracted from the BIOBADASER (Spanish Society of Rheumatology Database on Biologic Products), a registry of patients with rheumatic conditions treated with TNF antagonists. The rates of active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
312
2
28

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 609 publications
(352 citation statements)
references
References 15 publications
10
312
2
28
Order By: Relevance
“…Our study also confirmed that, as emphasized by other investigators (8), anti-TB chemoprophylactic treatment is efficient for preventing TB. None of our patients with TB had received a correct prophylactic antibiotic against TB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also confirmed that, as emphasized by other investigators (8), anti-TB chemoprophylactic treatment is efficient for preventing TB. None of our patients with TB had received a correct prophylactic antibiotic against TB.…”
Section: Discussionsupporting
confidence: 91%
“…Most cases of TB develop soon after treatment initiation and correspond to reactivation of a latent TB infection (4,5). Scientific organizations and health authorities worldwide have proposed recommendations for screening patients with latent TB infection and treating such patients before initiating anti-TNF treatment, and the effectiveness of these recommendations has been demonstrated (8).…”
mentioning
confidence: 99%
“…Implementation failures commonly relate to factors extrinsic to the guidelines; however, intrinsic factors contribute as well (9 -11). In a previous study, we estimated that in roughly 20% of patients in BIOBA-DASER, the physician failed to follow recommendations to manage LTBI, and we wondered about the future impact of this setback on the rate of new ATB (2). A straightforward explanation was not identified, although we believed that the increasing surplus of work represented for these new therapies was at play.…”
Section: Discussionmentioning
confidence: 97%
“…The recommendations include 9 months of isoniazid (INH) treatment for patients falling into one of the following categories: 1) a tuberculin skin test (TST) result Ն5 mm or a 2-step TST result Ն5 mm (if the first result was Ͻ5 mm); 2) a chest radiograph showing evidence of past tuberculosis; and 3) exposure to ATB or prior partially treated ATB. The significant impact of these recommendations was published elsewhere (2). Following this salient impact, new ATB cases were reported at a much lower rate.…”
Section: Introductionmentioning
confidence: 92%
“…Calendar time was modeled by including multiple indicator terms to adjust for possible changes in DMARD choice during the study period and possible changes in the prevention of serious infections in this population (24). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%